Effect of pre and post emergence herbicides on growth parameters in tomato cv. Arka vikas - K.SASIKALA, M.VENKATESWARA REDDY, K.UMAJYOTHI, P.SYAM SUNDAR REDDY and (The Journal of Research, PJTSAU, 2017)
A filed experiment was conducted to find out the best weed management practices in Tomato cv.Arka vikas during rabi 2011-12 and 2012-13. The experiment consisted of 10 treatments of Pre and post emergence (Pendimethalin, Oxyflourfen, Imazethapyr and Quizalofop ethyle) herbicides and their combination which were replicated thrice in Randomized block design. All the weed control treatments significantly influenced the growth attributes and yield such as plant height, No. of branches per plant, Leaf area Index (LAI), Plant dry matter and Yield. Hand weeding has recorded the maximum values for these attributes, however application of Pre emergence herbicides coupled with Quizalofop ethyle as post emergence found to be on par with Hand weeding. Imazethapyr applied as post emergence herbicide alone and combined with pre emergence herbicides recorded lower values than Weedy check as it is found to be extremely toxic to the crop.